2010
DOI: 10.1586/erv.10.89
|View full text |Cite
|
Sign up to set email alerts
|

Nano-microparticles as immune adjuvants: correlating particle sizes and the resultant immune responses

Abstract: The development of novel immune adjuvants is emerging as a significant area of vaccine delivery based on the continued necessity to amplify immune responses to a wide array of new antigens that are poorly immunogenic. This article specifically focuses on the application of nanoparticles and microparticles as vaccine adjuvants. Many investigators are in agreement that the size of the particles is crucial to their adjuvant activities. However, reports on correlating the size of particle-based adjuvants and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
380
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 471 publications
(389 citation statements)
references
References 105 publications
(174 reference statements)
8
380
0
1
Order By: Relevance
“…Our findings here are similar to our previous observations using this adjuvant and delivery system with a model antigen (ovalbumin). 37 They are also consistent with reported studies showing T H 1-biased enhancement of other protein antigens when combined with CpG ODN in PLGA nanoparticles. [48][49][50] Other therapeutic vaccines against Chagas disease have been found to induce a protective antigen-specific CD8 C T cell population that expands upon challenge with infection and produces T H 1-associated cytokines that include IFNg and TNFa, 51 as well as a CD4 C T cell population capable of IFNg production.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings here are similar to our previous observations using this adjuvant and delivery system with a model antigen (ovalbumin). 37 They are also consistent with reported studies showing T H 1-biased enhancement of other protein antigens when combined with CpG ODN in PLGA nanoparticles. [48][49][50] Other therapeutic vaccines against Chagas disease have been found to induce a protective antigen-specific CD8 C T cell population that expands upon challenge with infection and produces T H 1-associated cytokines that include IFNg and TNFa, 51 as well as a CD4 C T cell population capable of IFNg production.…”
Section: Discussionsupporting
confidence: 92%
“…therapeutic efficacy in mice will be translatable to humans, additional studies in non-human primates will be needed before moving the vaccine to the clinic. Lastly, while the PLGA nanoparticle production method employed in this paper is a common method that has been previously published, 37 debate exists as to the ideal size of nanoparticles for vaccine delivery. Some reports suggest that "viral-size" nanoparticles may enhance the immune response, while other studies report that larger particles elicit a better immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, it has been reported that very large-sized particles ranging from 50-100 m (which is larger than a typical APC) were least likely to be taken up by APCs, resulting in the generation of a low immune response. 31 Conjugates 6 and 7 formed large microparticles (143 µm and 106 µm, respectively), while construct 5 formed large, highly polydisperse aggregates (laser diffraction could not determine their sizes). Therefore, limited improvement in the efficacy upon incorporation of the E6 epitope into polymer-based vaccine might be related to the hydrophobic properties of the epitope, which cause extensive aggregation of the conjugates bearing it.…”
Section: In Vivo Tumor Treatmentsmentioning
confidence: 97%
“…30, 31,32 Large particles usually have an efficient depot effect for continuous antigen release. 31,33 We have proven that polyacrylate polymers conjugated to the E7 epitope formed microparticles (12-17 m), which were able to be efficiently taken up by APCs (including macrophages and dendritic cells), as well as to activate CD8 + and CD4 + cells to elicit adequate cellular immune responses against E7-expressing tumors. 14 However, it has been reported that very large-sized particles ranging from 50-100 m (which is larger than a typical APC) were least likely to be taken up by APCs, resulting in the generation of a low immune response.…”
Section: In Vivo Tumor Treatmentsmentioning
confidence: 99%